MAKNA KUALITAS LAYANAN MENURUT KARYAWAN HOTEL DI KAWASAN PARIWISATA UBUD, BALI - Eko Moh. Romi Kurniawan; I Putu Subiantara (Bajang Institute, 2026)
This study aims to explore the meaning of service quality from the perspective of hotel employees in the tourism area of Ubud, Bali, which is well known as a cultural and spiritual tourism destination. Unlike previous studies that predominantly assess service quality from the tourists’ perspective, this research emphasizes hotel employees as key actors in the service delivery process. A qualitative descriptive approach was employed. The informants consisted of hotel employees directly involved in guest services, including front office, housekeeping, food and beverage staff, as well as operational supervisors, selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the meaning of service quality among hotel employees in Ubud encompasses three main dimensions: professionalism in service delivery, sincerity and hospitality in interactions, and the integration of Balinese local cultural values, particularly the principle of Tri Hita Karana. Service quality is not merely understood as compliance with operational standards, but also as a relational process imbued with moral, ethical, and cultural values. These findings indicate that service quality in Ubud hotels is multidimensional and contextual, suggesting that hotel management should develop service quality improvement strategies that go beyond efficiency and guest satisfaction by incorporating employees’ perspectives and local cultural values.